Implementasi Prinsip Kehati-Hatian Dalam Perjanjian Kredit Berbasis Online - Rully Baidlowi; Arief Rahman (Fakultas Hukum Universitas Mataram, 2022)
This study aims to determine the process and what factors affect the implementation of the prudential banking principle in online-based agreements. This normative-empirical legal research method is basically a combination of normative legal approaches with the addition of various empirical elements with the Statute Approach, Conceptual Approach and Sociological Approach. Based on the results of the research, the application of the prudential banking principle in online-based credit agreements implemented by bank Danamon has complied with the prudential banking principle with the 5C of Credits element implemented by Bank Danamon are in accordance with Bank Indonesia regulations, Financial Services Authority regulations, and other laws and regulations. Other applicable laws and factors that influence this implementation are legal and non-legal factors.